A qualitative evaluation of an implementation study for cryptococcal antigen screening and treatment in Uganda. Issue 31 (August 2018) - Lofgren, Sarah M.; Nalintya, Elizabeth; Meya, David B.; Boulware, David R.; Rajasingham, Radha
Abstract : Abstract: Cryptococcal meningiti s causes 15% of AIDS-related deaths globally. Screening and preemptive treatment for cryptococcal antigen (CrAg) in the blood of persons with advanced HIV/AIDS reduces mortality. National and international HIV guidelines recommend CrAg screening; however, implementation studies and evaluations of how to integrate CrAg screening programs into existing HIV care infrastructure are lacking. During a CrAg screening program in Kampala, Uganda, we interviewed 15 health care workers (2 coordinating research nurses and 13 clinic personnel) from 6 HIV clinics between March and April 2017, to identify barriers to implementation as well as facilitating factors for program success. The interviews were coded and themes compiled. We found key factors for successful implementation of a CrAg screening program were: adequate supplies of fluconazole and CrAg lateral flow assay (LFA) point-of-care tests, timely patient follow-up, and quick turnaround time of laboratory results. Although both CrAg LFA kits and fluconazole are on the national formulary, stockouts are common, affecting patient care. The CrAg screening recommendation by national HIV guidelines remains integral to the success of the program, as overburdened clinics are otherwise reluctant to adopt additional screening. Collaboration with Ministries of Health for support with enforcing national guidelines, and procuring supplies is paramount to a successful CrAg screening program. Development of a CrAg screening and treatment program within the HIV clinic infrastructure has a number of barriers. Education and training of clinic staff, along with partnership with the Ministry of Health to ensure adequate supplies, facilitated the program.